The inter-relationship between physical activity, cardiorespiratory fitness, body composition and cardiometabolic risk factors in adults and children with cerebral palsy - Ryan, Jennifer (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Physiotherapy, 2014)
The association between physical activity, delayed all-cause mortality, decreased risk of hypertension, coronary heart disease, stroke and type II diabetes mellitus is well established. Physical activity has a positive effect on a number of cardiometabolic risk factors in adults and children including systolic blood pressure, triglycerides, high density lipoprotein-cholesterol, plasma glucose, insulin, and insulin resistance. It has been established that adults and children with cerebral palsy participate in less physical activity than their able-bodied peers. The aim of this thesis was to investigate the effect of reduced participation in physical activity on body composition, cardiorespiratory fitness, and cardiometabolic risk factors in adults and children with cerebral palsy.
Keywords: Physiotherapy, Ph.D.; Ph.D. Trinity College Dublin